2023
DOI: 10.1021/acs.jafc.3c04419
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Chlorogenic Acid in Escherichia coli Via Modular Pathway and Cofactor Engineering

Lian Wang,
Huijing Wang,
Jianbin Chen
et al.

Abstract: Chlorogenic acid is a natural phenolic compound widely used in the food and daily chemical industries. Compared to plant extraction, microbial cell factories provide a green and sustainable production method for the production of chlorogenic acid. However, complex metabolic flux distribution and potential byproducts limited the biosynthesis of chlorogenic acid in microorganisms. A de novo biosynthesis pathway for chlorogenic acid was constructed in Escherichia coli via modular engineering. Increasing the shiki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The MG09 and BD07 strains in the synthetic consortium are obligatory cooperators through cross-feeding of tyrosine and phenylalanine and are compatible in glucose and xylose mixture. Meanwhile, this is the first time metabolizing the cheap cellulosic sugars as carbon sources for the biosynthesis of CGA would make the fermentation of CGA cost-effective . Overall, we achieved de novo bioproduction of 131.31 ± 7.89 mg/L CGA using a rationally designed syntrophic two-strain coculture from low-cost xylose and glucose.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The MG09 and BD07 strains in the synthetic consortium are obligatory cooperators through cross-feeding of tyrosine and phenylalanine and are compatible in glucose and xylose mixture. Meanwhile, this is the first time metabolizing the cheap cellulosic sugars as carbon sources for the biosynthesis of CGA would make the fermentation of CGA cost-effective . Overall, we achieved de novo bioproduction of 131.31 ± 7.89 mg/L CGA using a rationally designed syntrophic two-strain coculture from low-cost xylose and glucose.…”
Section: Discussionmentioning
confidence: 96%
“…Meanwhile, this is the first time metabolizing the cheap cellulosic sugars as carbon sources for the biosynthesis of CGA would make the fermentation of CGA cost-effective. 49 Overall, we achieved de novo bioproduction of 131.31 ± 7.89 mg/L CGA using a rationally designed syntrophic two-strain coculture from low-cost xylose and glucose. The result demonstrated that the precise design and manipulation of the genome and chromosomes via gene editing advanced the carbon flux rewritten in the platform strains.…”
Section: Discussionmentioning
confidence: 96%
“…However, obtaining secondary metabolites using the technique of in vitro plant cultures also has disadvantages, such as low biomass yield, higher production costs, the maintenance of a controlled environment, the need for specialised manpower, a small number of profitable large-scale plants and the high cost and complexity of extraction, purification and analysis of the produced metabolites [ 105 ]. Consequently, chlorogenic acid can also be obtained by other techniques, such as fungal culture [ 106 ], bacterial cultivation [ 107 ] and fermentation of coffee pulp [ 108 , 109 ]. The most effective treatment of the fungus Saccharomyces cerevisiae studied has a higher yield of chlorogenic acid (234.8 mg/L) than Berula erecta culture grown under the most effective combined elicitation in the present study [ 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most effective treatment of the fungus Saccharomyces cerevisiae studied has a higher yield of chlorogenic acid (234.8 mg/L) than Berula erecta culture grown under the most effective combined elicitation in the present study [ 106 ]. The most effective strain of bacterium Escherichia coli tested also had a much higher yield of chlorogenic acid (472.0 mg/L) compared to the tissue culture of Berula erecta [ 107 ]. The yield of chlorogenic acid obtained by fermentation of coffee pulp in the da Silveira study was much lower (15 mg/L, after 8 h of coffee pulp fermentation with yeast A) than the yield of chlorogenic acid in Berula erecta in the present study [ 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Chlorogenic acid (CGA), a significant bioactive polyphenol, exhibits various pharmacological properties and biological activities, including antibacterial, antiviral, leukocyte-elevating, anti-adipogenic, and central nervous system stimulating effects. 37 Consequently, there is a pressing need for the selective separation of CGA from complex sample matrices. Several methods have been developed for extracting polyphenols from plant samples, including solvent extraction methods (including ultrasound-assisted extraction, and microwave-assisted extraction), supercritical fluid extraction, and SPE utilizing C 18 .…”
Section: Introductionmentioning
confidence: 99%